Robotic-Assisted Sleeve Lobectomy Using the Four-Arm Technique in the DaVinci Si® and Xi® Systems - Egberts, Jan-Hendrik; Möller, Thorben; Becker, Thomas (The Thoracic and Cardiovascular Surgeon, 2019)
Sleeve lobectomy (SL) makes it possible to resect centrally located lung carcinoma oncological correct while protecting healthy lung tissue. However, this procedure is often limited with conventional video-assisted thoracoscopic surgery, due to the limited mobility of the rigid and long instruments and the limited visualization. Therefore, these interventions are often still performed in the open conventional technique with the well-known disadvantages. Particularly in the reconstruction of the respiratory tract, precise sewing must be performed in a small space to avoid stenosis of the different diameter of the lumina. Robotic surgery offers several advantages through an enlarged three-dimensional view and flexibility of the robotic instruments, which are particularly evident when sewing. So far, there are only a few reports of robotic SL. Here, we describe our experience of performing robotic SL with four arms on both, the currently available DaVinci Xi® and Si® systems.
Keywords: lung; surgery; robotic; RATS; sleeve lobectomy